Estimating obstructive sleep apnea in Cyprus: a randomised, stratified epidemiological study using STOP-Bang sleep apnea questionnaire - Frangopoulos, Frangiskos; Nicolaou, Ivi; Zannetos, Savvas; Economou, Nicholas-Tiberio; Adamide, Tonia; Georgiou, Andreas; Trakada, Georgia (Sleep medicine, 2019)
Several epidemiological studies have demonstrated that Obstructive Sleep Apnea (OSA) is a highly prevalent disorder in the general population and increases over time all over the world. The high prevalence is in part due to increasing rates of obesity. However, estimates of OSA prevalence in Southern Europe are generally lacking. The aim of our study was to predict the risk of OSA in the general population of Cyprus, the southeast part of Europe, by using a dedicated questionnaire like STOP-Bang. We screened 5736 sample housing units for eligible adults and a total population of 4118 eligible responders completed the STOP-Bang questionnaire. Participants were all adults, age 18 + residing in Cyprus. The sample was stratified according to the last demographic report (2016) by district, rural or urban area, gender and age and the estimated sample size needed was 2000. Our survey was conducted by Computer Aided Telephone Interviewing (CATI) method. The question about Neck Circumference was removed from the final evaluation due to the uncertainty of most of the participants and the risk of bias. From a total of 4118 participants (2252 males – 54.7%, 1862 females – 45.3%), with 46.6% over 50 years old, 2641 (64.1%) were at low risk for OSA (0–2 positive answers), 1200 (29.1%) at intermediate risk (3–4 positive answers) and 277 (6.7%) at high risk (≥5 positive answers). In sum, 29.9% responded positively for snoring, 39.3% for feeling tired or sleepy during the day, 12.3% for observed apnea during sleep, and 24.6% for having or being treated for hypertension. Class II and III obesity with Body Mass Index (BMI) > 35 kgr/m2 was observed in 192 subjects (4.7%). In the subpopulation of obese participants (BMI>30 kg/m2), intermediate to high risk of OSA was present in 45%, whereas in obesity class II and III the percentage reached almost 90%. Our survey yielded that the prevalence of intermediate to high risk for OSA was 50% in males and 18% in females, in the general population of Cyprus. These findings were similar to previously reported high OSA prevalence worldwide, considering the fact that a single questionnaire is only a screening tool and cannot alone diagnose sleep apnea. •More than 1/3 of our population was categorized as intermediate to high risk of OSA.•The risk was higher within the 51–70 years old age group, for males, and in participants with higher BMI.•Women aged under 30 y (17.8%) and > 40 y (16.9%), reported snoring more often than women between 30 and 40 y (9.3%).•The most common symptoms of apnea tend to increase progressively over the age of 60 y and decrease later in life.•There were no significant differences between rural and urban populations in Cyprus concerning OSA symptoms.